2019
DOI: 10.3389/fmolb.2019.00140
|View full text |Cite
|
Sign up to set email alerts
|

Gender-Related Differences in Sickle Cell Disease in a Pediatric Cohort: A Single-Center Retrospective Study

Abstract: Sickle cell disease (SCD) is one of the most common monogenic disease worldwide. The incidence of SCD is not strictly gender-related as it is transmitted as an autosomal recessive disorder. In particular, the gender-related differences in pediatric SCD are not well-characterized. To address this matter, we retrospectively analyzed the clinical records of 39 pediatric patients with a diagnosis of SCD (hemoglobin SS genotype) focusing on gender differences analyzing various aspects of the disease and comprising … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 23 publications
(27 reference statements)
3
25
0
Order By: Relevance
“…The fact that male and female SCD patients display different symptoms is in agreement with currently available literature (Ceglie et al, 2019). Investigating the effects of sex and age on the expression of the disease is important because the manifestations may change with the passing of the years, and because the sexes may experience different numbers or severity of symptoms.…”
Section: Discussionsupporting
confidence: 85%
“…The fact that male and female SCD patients display different symptoms is in agreement with currently available literature (Ceglie et al, 2019). Investigating the effects of sex and age on the expression of the disease is important because the manifestations may change with the passing of the years, and because the sexes may experience different numbers or severity of symptoms.…”
Section: Discussionsupporting
confidence: 85%
“…Gender differences observed might be attributed to parental and cultural practice, as well as implication of disease severity on health. For example, males with SCA aged 3 months–11 years experienced more pain crises than females per year [ 57 ], which could contribute to the shorter sleep duration observed in our study. Research in a cohort of Chinese children (6–12 years) identified that the strongest predictor for bedtime and waketime in children were school start time, media use, maternal bedtime and waketime, extracurricular activities (e.g., delaying bedtime) and socioeconomic status (e.g., more homework delaying bedtime) [ 58 ].…”
Section: Discussionmentioning
confidence: 98%
“…It is likely that this reflects the sickling of red blood cells occurring during the crisis." It would be also interesting to explore the sexual dimorphism of these sickle mice metabolomic signatures, which may explain the sex-related specificity of the clinical expression that has been reported [41].…”
Section: Discussionmentioning
confidence: 99%
“…However, during the vaso-occlusive crisis in humans, the phosphatidylcholines and lysophosphatidylcholines are mostly increased, while they are drastically reduced in the mouse model in steady state. It is likely that this reflects the sickling of red blood cells occurring during the crisis.” It would be also interesting to explore the sexual dimorphism of these sickle mice metabolomic signatures, which may explain the sex-related specificity of the clinical expression that has been reported [ 41 ].…”
Section: Discussionmentioning
confidence: 99%